A taste of ambrosia: Do Olympic medalists live longer than Olympic losers? - Kovbasiuk, A.; Ciechanowski, L.; Jemielniak, D. (Scandinavian Journal of Public Health, 2025)
Objective: To investigate the longevity of a large sample of Olympic Games participants, considering the interaction between different types of sports and medal awards.